FIX&FOXYs distribuering af ledelse - Krøgholt, Ida (Peripeti, 2022)
FIX&FOXYs distribuering af ledelse by Ida Krøgholt. Krøgholt is unfolding FIX&FOXY’s way of working as distributed facilitation, where the participants facilitate each other, and thus through the theatre process develop an awareness of communication and observation.